Influence of novel oral anticoagulants on anticoagulation care management - Janzic Andrej; Kos Mitja (Acta Pharmaceutica)
Anticoagulation treatment was recently improved by the introduction of novel oral anticoagulants (NOACs). Using a combination of qualitative and quantitative methods, this study explores the effects of the introduction of NOACs on anticoagulation care in Slovenia. Face-to-face interviews with key stakeholders revealed evolvement and challenges of anticoagulation care from different perspectives. Obtained information was further explored through the analysis of nationwide data of drug prescriptions and realization of health care services. Simplified management of anticoagulation treatment with NOACs and their high penetration expanded the capacity of anticoagulation clinics, and consequentially the treated population increased by more than 50 % in the last 5 years. The main challenge concerned the expenditures for medicines, which increased approximately 10 times in just a few years. At the same time, the anticoagulation clinics and their core organisation were not affected, which is not expected to change, since they are vital in delivering high-quality care.